Faktor Psikologi Marketing Dalam Mempengaruhi Perilaku Konsumen "Decoy Effect" Membeli Produk Yang Lebih Mahal - Rajagukguk, Frederick Rudy Sentosa (Economic Development Progress, 2024)
This research is about Marketing Psychological Factors: Influencing Consumer Behavior "Decoy Effect" Buying More Expensive Products. In this research, the approach used by researchers is a quantitative approach. Data analysis techniques are used to answer problem formulations or test hypotheses that have been formulated. In hypothesis testing, it can be seen from the t-statistic value and probability value. The research results of the first hypothesis are accepted that Marketing Psychology (X) influences the Decoy Effect (Z). The second hypothesis is accepted that the Decoy Effect (Z) influences Consumer Behavior (Y). The third hypothesis is accepted that Marketing Psychology (X) has a significant effect on Consumer Behavior (Y) through the Decoy Effect (Z) as an intervening variable.